A Case Study of Two Rodent-Borne Viruses: Not Always the Same Old Suspects - Childs, James E.; Klein, Sabra L.; Glass, Gregory E. (Frontiers in Ecology and Evolution, 2019)
Two Old World rodents, the house mouse (Mus musculus) and the Norway rat (Rattus norvegicus) have been introduced into and established populations on every Continent save Antarctica. With their travels they have carried various human pathogens. Two viruses- Lymphocytic choriomeningitis virus (LCMV; genus Arenavirus with mice) and Seoul virus (SEOV; genus Hantavirus with rats) - can cause chronic infections within their respective rodent hosts resulting in persistent or life-long sporadic shedding of virus through secreta and excreta. Although the prevalence of infection within their wild rodent hosts can exceed 25% among mice infected with LCMV and 50% among rats infected with SEOV, acute human disease resulting from direct transmission from wild rodents are rarely reported even though both species live in close coexistence with humans. However, the usual ‘classic’ zoonotic cycle of transmission from wild rodent reservoirs to humans now includes multiple unusual/unexpected routes. The largest described outbreaks of human disease caused by these viruses are linked to pet rodents. SEOV outbreaks are linked to fancy rats kept as pets, and, a novel reservoir host, the Golden hamster, has supplanted the house mouse as major source of LCMV infection. Following LCMV, and to a lesser extent SEOV, outbreaks associated lab animals, have led to 100’s of cases of LCMV among owners of pet hamsters. LCMV infections in research settings have also been traced to mouse-derived cell cultures and nude mice. Additionally, LCMV is now a recognized source of severe congenital disease and is the unexpected source of severe and often fatal disease among solid organ recipients. Although the extensive usual and unusual routes of LCMV infection are exceptional there are many parallels with SEOV emergence.